Analysis of Sustainable Mobility in Cities: Piura Case 2025 and Comparison with Peruvian Cities - La Rosa-Boggio, Diego Orlando; Torres Samillán, Rosa Amelia; Zulueta Cueva, Carlos Eduardo; Ruíz Sime, Pedro Henrry Alejandro; Coloma Castillo, Elena Estefanía; Miranda Flores, Javier Nestor (LACCEI, 2025)
Sustainable urban mobility (SSM) is a key global challenge, impacting climate change, quality of life and social equity. This systematic review, based on academic literature from 2020 to 2025 and following the PRISMA 2020 method, analyzes the MUS in Peruvian intermediate cities such as Piura, Trujillo, Arequipa and Cajamarca. Globally, there is a trend towards reduced use of private vehicles, shared mobility and the incorporation of smart technologies, while in Latin America problems such as informal growth and unequal access to transport persist. In Peru, transport is a major emitter of polluting gases and cities face congestion, informality and lack of equity.The study highlights a gap between national policies and their local implementation. It concludes that there is an urgent need to adopt integrated approaches that prioritize active mobility and efficient public transport, addressing informality and inequity. In addition, it highlights the need for empirical research to assess the impact of policies on intermediate cities, to guide decisions towards more sustainable and equitable urban development in Peru.